Near Complete Repair After Myocardial Infarction in Adult Mice by Altering the Inflammatory Response With Intramyocardial Injection of α-Gal Nanoparticles - Galili, Uri; Zhu, Zhongkai; Chen, Jiwang; Goldufsky, Josef W.; Schaer, Gary L. (Frontiers in Cardiovascular Medicine, 2021)
Background: Neonatal mice, but not older mice, can regenerate their hearts after myocardial-infarction (MI), a process mediated by pro-reparative macrophages. α-Gal nanoparticles applied to skin wounds in adult-mice bind the anti-Gal antibody, activate the complement cascade and generate complement chemotactic peptides that recruit pro-reparative macrophages which are further activated by these nanoparticles. The recruited macrophages decrease wound healing time by ~50%, restore the normal skin structure and prevent fibrosis and scar formation in mice. Objectives: The objective of this study is to determine if α-gal nanoparticles injected into the reperfused myocardium after MI in adult-mice can induce myocardial repair that restores normal structure, similar to that observed in skin injuries. Methods and Results: MI was induced by occluding the mid-portion of the left anterior descending (LAD) coronary artery for 30 min. Immediately following reperfusion, each mouse received two 10 μl injections of 100 μg α-gal nanoparticles in saline into the LAD territory (n = 20), or saline for controls (n = 10). Myocardial infarct size was measured by planimetry following Trichrome staining and macrophage recruitment by hematoxylin-eosin staining. Left ventricular (LV) function was measured by echocardiography. Control mice displayed peak macrophage infiltration at 4-days, whereas treated mice had a delayed peak macrophage infiltration at 7-days. At 28-days, control mice demonstrated large transmural infarcts with extensive scar formation and poor contractile function. In contrast, mice treated with α-gal nanoparticles demonstrated after 28-days a marked reduction in infarct size (~10-fold smaller), restoration of normal myocardium structure and contractile function. Conclusions: Intramyocardial injection of α-gal nanoparticles post-MI in anti-Gal producing adult-mice results in near complete repair of the infarcted territory, with restoration of normal LV structure and contractile function. The mechanism responsible for this benefit likely involves alteration of the usual inflammatory response post-MI, as previously observed with regeneration of injured hearts in adult zebrafish, salamanders and neonatal mice.